Respuestas
Respuesta dada por:
0
Respuesta:
Así me salió.
Adjuntos:
![](https://es-static.z-dn.net/files/dcf/d46c266bc8c70fca7e730d1a3ad4dec0.jpg)
Respuesta dada por:
1
Respuesta:
- 2
Explicación paso a paso:
(1+senx+xosx)(1-senx-cosx)/senxconx
(1+senx+cosx)(1-(senx+cosx))/senxcosx
(1² - (senx + cosx)²)/senxcosx =
(1 - (1 + 2senxcosx))/senxcosx =
(1 - 1 - 2senxcosx)/senxcosx =
(- 2senxcosx)/senxcosx =
- 2
Preguntas similares
hace 5 años
hace 5 años
hace 8 años
hace 8 años
hace 8 años
hace 9 años
hace 9 años